EFFECTIVENESS OF IMMUNOSUPPRESSANTS IN THE TREATMENT OF JUVENILE IDIOPATHIC ARTHRITIS IN CHILDREN (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article presents the results of a comparative study of the effectiveness of leflunomide and methotrexate in children with juvenile idiopathic arthritis. The study included 96 children aged 2 to 16 years: the main group included 56 children treated with leflunomide, the comparison group included 40 patients treated with methotrexate in an average dose. Therapy with leflunomide was significantly more effective than methotrexate in standard doses. A clear improvement in children treated with leflunomide was observed after 12 weeks. 15% of patients had inactive disease. In children from the comparison group, systemic manifestations continued to recur, active arthritis persisted, laboratory values were high, and disability progressed.